Analisis Kekuatan Hukum Internasional dalam Kasus Surat Penangkapan ICC oleh Vladimir Putin dalam Konflik Rusia-Ukraina - Zahrani, Nurul Avida; Burhanuddin, Agussalim (CV Insan Kreasi Media, 2023)
The Russia-Ukraine conflict, which began in 2022, has enormous significance, so that the war continues to flare up, inviting international organizations to react. Various acts of war carried out both in order to achieve victory. Starting from gun battles in border areas, cyber-attacks to the most severe cases where there are indications of war crimes. So that this war ended up inviting an international reaction, especially the International Court of Justice. The emergence of ICC accusations against Russia for adopting Ukrainian children. Making Vladimir Putin accused of war crimes and will be made a suspect by the ICC Court.This study uses a qualitative descriptive research method by collecting data from literature studies. The results of this study found that in international law the ICC could not arrest Vladimir Putin for war crimes against the adoption of children in Ukraine. In its jurisdiction, the ICC has absolutely no power to convict Putin as a suspect in these war crimes. Not to mention the power that Vladimir Putin has in the international world. With the power he has, Vladimir Putin is not affected by the threat of an arrest warrant by the ICC. Keywords: Russian-Ukrainian conflict, ICC, Vladimir Putin, Russia, International Criminal Law, Hegemony of power, International Law